Desempeño en la Detección de Nódulos Mamarios del Examen Clínico de Seno Realizado por Examinadoras Invidentes Comparado con Ultrasonido - Luis Alberto Olave Asprilla; Diego Fernando Botero Henao; Yiset Adriana Fernández De Córdoba Florez (Universidad Libre, 2021)
Resumen. Introducción: Clinical examination of the breast is a simple method to detect nodules, which is useful to determine its nature, of low cost, non-invasive and of great value as a diagnostic tool when necessary. Traditionally, clinical examination is carried out by trained health personnel with a sensitivity of 54% and a specificity of 94%; it is unknown its usefulness compared to mammography, since the physical examination in patients without previous screening has not been evaluated. Objetivo: to determine the performance of the clinical examination of tactile auxiliary examiners for detecting mammary nodules, compared with the ultra-sonography findings in the detection of mammary nodules. Métodos: a validation study of diagnostic tests was carried out with a random sample of 325 women from the San Juan de Dios Hospital, aged between 18 and 70 years, during a period of 2 months. Resultados: The sensitivity was 64.8% (95% CI 57.5-71); specificity, 45.6% (95% CI 37.8-53.6); positive predictive value, 58.5% (95% CI 51.4-65.1); negative predictive value, 52.3% (95% CI 43.8-60.7). Proportion of false positives, 54.4% (95% CI 46.4-62.2); proportion of false negatives, 35.2% (95% CI 28.6-42.5). Conclusión: The study showed that the clinical examination of the breast by trained personnel with visual impairment is a diagnostic test sensitive to the detection of mammary nodules; but it has little specificity. In addition, it is a complement to screening for mammary pathology, even though it does not replace the medical examination nor the screening tests recommended by the clinical practice guidelines.